Visual nursing : a guide to diseases, skills, and treatments (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
This colorful book for practicing nurses and nursing students provides a unique approach to learning important clinical concepts and techniques. It presents information in a remarkably clear and easy-to-understand fashion, using abundant illustrations to demonstrate hands-on treatments and explain disease pathophysiology. Fully visual text lets the nurse read less and understand more, improving her skills and gaining confidence as a health professional through pictures. Includes hundreds of color illustrations, photographs, wave forms, diagrams, and morecreative visuals; concise, step-by-step instructions to help build nurse's confidence and alleviate fear of hands-on treatments; disease pathophysiology depicted clearly; visual presentation of topics, to make it simple to learn complicated techniques; "Lesson Plans" icon signals important information to teach the patient; "Picturing Patho" icon points to anatomical illustrations demonstrating what happens when a disease occurs; "Hands On" icon shows the nurse how to perform nursing proceduresand techniques and administer treatments. - Publisher.